The New Generation of Computable General Equilibrium Models Modeling the Economy (Springer International Publishing, 2018)
This book covers some important topics in the construction of computable general equilibrium (CGE) models and examines use of these models for the analysis of economic policies, their properties, and their implications. Readers will find explanation and discussion of the theoretical structure and practical application of several model typologies, including dynamic, stochastic, micro-macro, and simulation models, as well as different closure rules and policy experiments. The presentation of applications to various country and problem-specific case studies serves to provide an informed and clearly articulated summary of the state of the art and the most important methodological advancements in the field of policy modeling within the framework of general equilibrium analysis. The book is an outcome of a recent workshop of the Italian Development Economists Association attended by a group of leading practitioners involved in the generation of CGE models and research on modeling the economy and policy making. It will be of interest to researchers, professional economists, graduate students, and knowledgeable policy makers. .